Pengaruh Pemberian Bokashi Tithonia (Tithonia diversifolia) Terhadap Pertumbuhan dan Hasil Tanaman Sawi Hijau (Brassica juncea L.) - Dia Azhari; Prima Novia; Meriati (Fakultas Pertanian, Universitas Ekasakti, 2022)
An experiment on the effect of giving bokashi tithonia on the growth and yield of mustard greens (Brassica juncea L.) was carried out in Korong Gadang Village, Kuranji District, Padang City, West Sumatra. This research was conducted from March to April 2019. The purpose of this study was to obtain the dose of bokashi tithonia. The study used a completely randomized design (CRD) with 6 treatments and 4 replications. The treatments were: A = Control (without Bokashi), B = Bokashi Tithonia 3 t.ha-1 (33.75 g tan-1), C = Bokashi Tithonia 6 t.ha-1 (67.5 g tan- 1), D = Bokashi Tithonia 9 t.ha-1 (101.3 g tan-1), E = Bokashi Tithonia 12 t.ha-1 (135 g tan-1), F = Bokashi Tithonia 15 t.ha- 1 (168.75 g tan-1). The data for each observation were obtained and analyzed by means of variance, if F count > F table, then it was continued with Duncan's New Multiple Range Test (DNMRT) at a significant level of 5%. The experimental results showed that the effect of giving Bokashi Tithonia on the growth and yield of mustard greens (Brassica juncea L.) had no significant effect on plant height, number of leaves, widest leaf width, plant fresh weight, while giving effect on longest leaf length. So that the best dose of Bokashi Tithonia has not been obtained for the growth and yield of mustard greens. Based on the above, it can be suggested to conduct research on Bokashi Tithonia at a rate higher than 15 tons/ha.